A circular patch antenna with parasitic element for UHF RFID applications. Issue 8 (7th April 2015) - Sim, C. Y. D.; Chen, C. C.; Cao, R.; Chen, B. S.
ABSTRACT This article initially proposes a directly‐fed circular patch antenna with L‐shaped ground plane for Radio Frequency Identification (RFID) applications in the 900 MHz (902−928 MHz) ultrahigh frequency (UHF) band. To achieve circularly polarized (CP) radiation, two arc‐shaped notches are loaded into the main patch. To enhance the CP bandwidth so that the proposed antenna can also cover the UHF RFID band for Europe (866−869 MHz), a parasitic element is printed besides the main patch. Experimental measurements show that the 10‐dB return loss bandwidth of the proposed antenna was 30.95% (833−1138 MHz) and its corresponding 3‐dB axial ratio bandwidth was 8.95% (865−946 MHz). Good gain and radiation efficiency of more than 7 dBic and 90%, respectively, were also exhibited across the two desired UHF RFID bands. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:681–687, 2015.